TRANSFORMASI PEMBELAJARAN MEMBACA DI SEKOLAH DASAR DARI BUKU TEKS KE LITERASI DIGITAL (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The transformation of reading instruction from traditional textbooks to digital literacy in elementary schools represents a significant shift in education to meet the demands of the digital era. This study aims to explore the implementation and impact of digital literacy on reading instruction, focusing on how it affects students’ engagement, comprehension, and critical thinking skills. Using a qualitative approach with case study design, the research investigates the experiences of teachers and students in schools that have integrated digital learning tools into their reading curriculum. The findings indicate that digital literacy enhances student engagement by providing interactive and multimodal content, allowing for a more comprehensive learning experience. However, challenges such as the digital divide, limited access to technology, and the need for teacher training were identified as barriers to successful implementation. Despite these challenges, the study highlights the potential of digital literacy to foster critical thinking, improve information access, and equip students with essential 21st-century skills. The research concludes that for a successful transformation of reading instruction, a balanced approach involving access to technology, teacher development, and relevant curriculum integration is essential.